Record keeping for your own business - Savage, Warwick, 1935-; Reynolds, Wal.; Williams, Alan. (South Melbourne : Nelson, 1994)
This book details a simple record-keeping system for a small business. It shows how to build a complete systems, and how records are kept in each part of that system...
Keywords: Bookkeeping; Small business -- Australia -- Accounting; Bookkeeping